Comparative transcriptomic analysis of Tibetan Gynaephora to explore the genetic basis of insect adaptation to divergent altitude environments. Issue 1 (December 2017) - Zhang, Qi-Lin; Zhang, Li; Yang, Xing-Zhuo; Wang, Xiao-Tong; Li, Xiao-Peng; Wang, Juan; Chen, Jun-Yuan; Yuan, Ming-Long
Abstract Adaptation of insects to different altitudes remain largely unknown, especially those endemic to the Tibetan Plateau (TP). Here, we generated the transcriptomes ofGynaephora menyuanensis andG. alpherakii, inhabiting different high altitudes on the TP, and used these and the previously available transcriptomic and genomic sequences from low-altitude insects to explore potential genetic basis for divergent high-altitude adaptation inGynaephora . An analysis of 5, 869 orthologous genes amongGynaephora and other three low-altitude insects uncovered that fast-evolving genes and positively selected genes (PSGs) in the twoGynaephora species were enriched in energy metabolism and hypoxia response categories (e.g. mitochondrion, oxidation-reduction process, and response to oxidative stress). Particularly, mTOR signaling pathway involving hypoxia was enriched by PSGs, indicating this well-known pathway in mammal hypoxia adaptation may be an important signaling system inGynaephora . Furthermore, some PSGs were associated with response to hypoxia (e.g. cytochrome proteins), cold (e.g. dehydrogenase) and DNA repair (e.g. DNA repair proteins). Interestingly, several insect-specific genes that were associated with exoskeleton and cuticle development (e.g. chitinase and ecdysteroids) had experienced positive selection, suggesting the specific adaptive mechanisms in insects. This study is favourable for understanding the adaptive evolution ofGynaephora and even TP insects to divergent altitudes.